Sociodemographic predictors of temperament and character - Mendlowicz, Mauro V; Jean-Louis, Girardin; Gillin, J.Christian; Akiskal, Hagop S; Furlanetto, Leticia M; Rapaport, Mark H; Kelsoe, John R (Journal of psychiatric research, 2000)
The Unified Biosocial Theory of Personality postulates that human personality is organized around four temperaments — Novelty Seeking, Harm Avoidance, Reward Dependence, and Persistence — and three characters — Self-Directedness, Cooperativeness, and Self-Transcendence. The objective of the present study was to investigate the influence of sociodemographic factors on temperament and character without the confounding influence of mental disorders. Volunteers ( n=94) did not meet criteria for any Axis I and Axis II diagnosis, had no first-degree relatives with mental disorders, and were medically healthy. After giving written informed consent, volunteers completed the Temperament and Character Inventory. Analyses were conducted to determine the degree of association of each sociodemographic factor (i.e., age, gender, ethnicity, marital status, educational attainment, and occupational status) to personality dimension, while controlling for possible interactions with other sociodemographic factors. Partial correlation analysis showed a significant association between gender and Reward Dependence, and occupational status was significantly related to Reward Dependence, Cooperativeness, and Self-Transcendence. Stepwise regression analysis indicated that gender and occupational status were significant predictors of Reward Dependence. Occupational status was the only predictor of Cooperativeness and Self-Transcendence. These data suggest that sociodemographic factors should be considered in studies investigating temperaments and characters as defined by the Unified Biosocial Theory of Personality.